Cycle E-racing: Simulation or a new frontier in sports technology? - Dryer, B. (International Journal of Esports, 2021)
Cycling-based e-racing is a growing sector of e-sports. Unlike more traditional forms of e-sports, it comprises a high level of physical exertion that is directly comparable to the activity it simulates in reality. However, as this activity has developed, it has also provided the basis for new forms of controversy. Additionally, it has provided the means for performance enhancement that, technologically speaking, could decouple the user from how they cycle in reality compared to how they are perceived within the virtual environment. Either way, the recent development of cycle-based e-racing provides an argument that it has transcended from being a simulation of cycle racing into a new form of competitive discipline in its own right.